Periodisasi Kajian Hadis di Indonesia: Tradisi Ulama Abad XVII hingga Diskursus Kontemporer: The Periodization of Hadith Studies in Indonesia: From the Scholarly Tradition of the 17th Century to Contemporary Discourse - Nur Malasari; Tasbih; Arifuddin Ahmad (AL ISNAD: Journal of Indonesian Hadith Studies, 2026)
This study aims to trace and analyze the historical development of hadith studies in Indonesia from the 17th century to the contemporary era. The method employed is qualitative research with a library research approach, using historical and descriptive-analytical analysis of relevant classical and modern literature. The findings indicate that hadith studies in Indonesia began in the 17th century through the contributions of Nusantara scholars such as Nuruddin al-Raniri, Abdurrauf as-Singkili, and Yusuf al-Makassari, who integrated hadith with Sufism, jurisprudence, and ethics. This development experienced stagnation in the 18th century but revived in the 19th century through Islamic educational institutions such as pesantren and madrasah, and further strengthened in the modern period with the inclusion of hadith studies in higher education and the growth of Islamic organizations. In the contemporary era, hadith studies have shown significant progress through the increase of academic research, scholarly publications, and the emergence of various forums and scholarly associations. In conclusion, hadith studies in Indonesia have developed dynamically and continuously, from classical to modern traditions, and play an important role in shaping the Islamic intellectual tradition in Indonesia.